Consumer and Their Rights In Insurance Sector: Ensuring Better Protection for Consumers (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In India, 24th December is celebrated as "NationalConsumer Rights Day", since the Consumer Protection Act, 1986 was enactedon this day. The Consumer Protection Act was enacted in 1986 based on UnitedNations guidelines with the objective of providing better protection ofconsumers’ interests. The Act provides for effective safeguards to consumers againstvarious types of exploitations and unfair dealings, relying on mainlycompensatory rather than a punitive or preventive approach.  It applies to all goods and services unlessspecifically exempted and covers the private, public and cooperative sectorsand provides for speedy and inexpensive adjudication.